ANALISIS POSTUR GERAKAN KERJA BARISTA NESTEH DENGAN ANGLE METER MENGGUNAKAN METODE RAPID UPPER ASSESSMENT - Syahrial Aman; Aisyah Noor Hidayati; Wahyu Cahaya Putri; Hanin Fitria; Sam'ani Intakoris (JURNAL TEKNOLOGI DAN MANAJEMEN INDUSTRI, 2025)
Doing work, especially as a barista, with the wrong working posture and designing tools that are not ergonomic can result in losses, one of which is complaints of musculoskeletal disorders.  The Rula method is a method of using target body postures to estimate the risk of injury.  The assessment using the Rula method is a systematic assessment of the risk of problems occurring by indicating the part of the worker's body that is experiencing the disorder.  Based on the results of these scores, the results are all the same but corrective action is still needed.  The calculation results for both working postures are based on the Rapid Upper Limb Assessment (RULA) method.  So the research aims to find out the working posture of Nestea barista employees and provide input into the incorrect body posture of working movements of employees.  The final result of data processing using the RULA method can be concluded that the assessment of the work posture of Nestea baristas, for the final process of making drinks, a score of three was obtained, and for packaging of drinks, a score of three was obtained. It can be concluded that the assessment of working postures is all the same with a score of three, but the three work postures still need to be changed.